Efficacy and safety results from a Phase 3, randomized, placebo‐controlled trial of subcutaneous golimumab in Chinese patients with active rheumatoid arthritis despite methotrexate therapy. (11th August 2015) - Li, Zhanguo; Zhang, Fengchun; Kay, Jonathan; Fei, Kaiyin; Han, Chenglong; Zhuang, Yanli; Wu, Zhong; Hsia, Elizabeth C.
Abstract: Aim: The efficacy and safety of golimumab + methotrexate (MTX) were evaluated in Chinese patients with active rheumatoid arthritis (RA) despite MTX therapy. Methods: Chinese patients ( n  =   264) were randomly assigned (1 : 1) to receive subcutaneous injections of placebo + MTX with crossover to golimumab 50 mg + MTX at week 24 (Group 1) or to golimumab 50 mg + MTX (Group 2) every 4 weeks. Group 1 patients with inadequate response entered blinded early escape to golimumab 50 mg + MTX at week 16. At least a 20% improvement in the American College of Rheumatology (ACR20) criteria at week 14 was the primary endpoint. Other assessments included the 28‐joint count Disease Activity Score using C‐reactive protein (DAS28‐CRP) and Health Assessment Questionnaire‐Disability Index (HAQ‐DI) through week 52. Adverse events (AEs) were monitored through week 56. Results: ACR20 response at week 14 was significantly higher in Group 2 (40.9% [54/132]) compared with Group 1 (15.9% [21/132]; P  <   0.001). Greater proportions of patients in Group 2 compared with Group 1 had a DAS28‐CRP response at week 14 (65.2% vs . 30.3%, P  <   0.001) or ACR20 response at week 24 (42.4% vs . 15.9%, P  <   0.001), and Group 2 had a significantly greater change in HAQ‐DI at week 24 (−0.26 vs . 0.15, P  <   0.001). After week 24, the proportion of patients achieving ACR20 in Group 1 approached that in Group 2. Through week 16, 23.5% of Group 1 and 26.7% of Group 2 patients reported AEs. Among golimumab + MTX‐treated patients, 50.2% and 4.2% had ≥ 1 AE or serious AE, respectively, through week 56. No unexpected safety signals were observed. Conclusion: Among MTX‐experienced Chinese patients with active RA, a significantly greater proportion of patients receiving golimumab + MTX had improvements in the signs and symptoms of RA compared with MTX monotherapy. Safety findings were consistent with previous studies of golimumab in patients with RA.